2017
DOI: 10.1097/tp.0000000000001455
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Virus Load—Inverse Association With Antibody-Mediated Rejection After Kidney Transplantation

Abstract: Background-Antibody-mediated rejection (ABMR) represents one of the cardinal causes of late allograft loss after kidney transplantation and there is great need for noninvasive tools improving early diagnosis of this rejection type. One promising strategy might be the quantification of peripheral blood DNA levels of the highly prevalent and apathogenic Torque Teno virus (TTV), which might mirror the overall level of immunosuppression and thus help determine the risk of alloimmune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 37 publications
(54 reference statements)
8
87
0
2
Order By: Relevance
“…(8) Similarly, low TTV viremia has been linked to a higher incidence of chronic allograft dysfunction in lung transplantation (15) and with antibody-mediated rejection in kidney transplantation. (16) Our results suggest a higher state of IS in patients who received triple IS: These patients presented significantly more episodes of CMV infection and had higher TTV DNA levels. In addition, all episodes of CMV disease were diagnosed in this group.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(8) Similarly, low TTV viremia has been linked to a higher incidence of chronic allograft dysfunction in lung transplantation (15) and with antibody-mediated rejection in kidney transplantation. (16) Our results suggest a higher state of IS in patients who received triple IS: These patients presented significantly more episodes of CMV infection and had higher TTV DNA levels. In addition, all episodes of CMV disease were diagnosed in this group.…”
Section: Discussionmentioning
confidence: 57%
“…Regarding posttransplant events in LT, negative viremia before transplant has been associated with a higher incidence of rejection . Similarly, low TTV viremia has been linked to a higher incidence of chronic allograft dysfunction in lung transplantation and with antibody‐mediated rejection in kidney transplantation …”
Section: Discussionmentioning
confidence: 99%
“…The replication kinetics observed in our cohort was similar to that previously reported in LT recipients, with a rapid increase in viral load from days 7 to 30, which was followed by a less pronounced slope thereafter, to peak beyond month 3 in most patients. 15,44 It should be noted that the alphatorquevirus doubling time was higher during the first posttransplant week than in the subsequent period until day 30, pointing to a certain delay in the triggering effect of iatrogenic immunosuppression on viral replication and shaping a sigmoid-like curve, which has also been observed after LT. 15 Recent studies have reported an association between low or undetectable alphatorquevirus viremia and an increased risk of graft rejection after lung, 24 kidney, 23 and liver transplantation. 22 Similarly to our experience, data from the Swiss Transplantation Cohort Study showed that 1-year cumulative incidence of rejection among liver transplant recipients with undetectable TTV DNA loads at transplantation were significantly higher than in patients with detectable titers.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In addition, some authors have reported a direct association between higher DNA loads and posttransplant infection. [22][23][24] In addition, some authors have reported a direct association between higher DNA loads and posttransplant infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation